Deoxycytidyl-Deoxyguanosine Oligonucleotide Classes A, B, and C Induce Distinct Cytokine Gene Expression Patterns in Rhesus Monkey Peripheral Blood Mononuclear Cells and Distinct Alpha Interferon Responses in TLR9-Expressing Rhesus Monkey Plasmacytoid Dendritic Cells - Abel, Kristina; Wang, Yichuan; Fritts, Linda; Sanchez, Eleonora; Chung, Eugene; Fitzgerald-Bocarsly, Patricia; Krieg, Arthur M.; Miller, Christopher J. (Clinical and Diagnostic Laboratory Immunology, 2005)
Classifications Services CVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CVI About CVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1556-6811 Online ISSN: 1556-679X Copyright © 2014 by the American Society for Microbiology. For an alternate route to CVI .asm.org, visit: CVI